Formação de professores da educação infantil: uma intervenção para orientação quanto ao aspecto psíquico do desenvolvimento de bebês - Ferreira, Sulyanne da Silva (Universidade Federal de São Carlos, 2022)
The present study is part of the research line "Management of Care, Work and Health Education". Specifically, in the focus of Labor Management, with emphasis on the learning needs of workers resulting from this process. It sought to perform an articulation between the contributions of the fields of Collective Health and Education, in order to build a practice committed to the care of children in early childhood who are in daycare centers, emphasizing health conditions based on aspects of the psychic constitution and development of babies. The objective was to verify the effects of an intervention based on the Methodology Risk Indicators for Child Development -IRDI on the educational action of teachers of a day care center. This was a qualitative and exploratory research, which has as its scenario a Municipal School of Early Childhood Education and Elementary School, in the city of Russas in the interior of Ceará. The technical procedure used by this study consisted of an action research through written Life Narratives deposited in letters. It is also noteworthy that the research was based on the theoretical and methodological contributions of Psychoanalysis in conjunction with the field of Collective Health. The technique for material analysis was performed through Discourse Analysis, as proposed by Michel Pêcheux (2006). Through the narratives, as well as the dialogues in the formation meetings, the middlemen involved in the relations between caring and educating in the context of daycare were observed. It was also pointed out the important contribution of formative processes as support to the practical making of teachers. The results of the study showed that, based on the proposal of didactic-dialogical training about the psychic constitution in conjunction with the practices of the nursery context, it was possible for teachers to apprehension about the notion of psychism and subjectivity intrinsic to the development of the small child. Through the construction of a space of speech, exchanges and resignifications, it was possible for the teachers to build new perspectives for their future practices, and that, in this view, would be present the mark of the singularity of relationships and their influence on the constitution of the subjectivity of the baby. It was also verified that the formation allowed the expansion of looking at the formulation of demands that are not only organic in nature, but also about the psychic constitution.
Training of early childhood education teachers: a intervention for guidance on the psychic aspect of the development of babies
Keywords: Formação de Professores; Constituição Psíquica; Desenvolvimento Infantil; Psicanálise; Teacher Training; Psychic Constitution; Child Development; Psychoanalysis; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA